2018
DOI: 10.1038/s41586-018-0352-3
|View full text |Cite
|
Sign up to set email alerts
|

Hurricane-induced selection on the morphology of an island lizard

Abstract: Hurricanes are catastrophically destructive. Beyond their toll on human life and livelihoods, hurricanes have tremendous and often long-lasting effects on ecological systems. Despite many examples of mass mortality events following hurricanes, hurricane-induced natural selection has not previously been demonstrated. Immediately after we finished a survey of Anolis scriptus-a common, small-bodied lizard found throughout the Turks and Caicos archipelago-our study populations were battered by Hurricanes Irma and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
128
2
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(139 citation statements)
references
References 31 publications
6
128
2
3
Order By: Relevance
“…Although it is difficult to demonstrate rapid evolution in nature, there is growing empirical evidence that when environmental selection is very intense, evolutionary processes may occur on a very fast time scale (Amorim et al, 2017;Donihue et al, 2018;Schoener, 2011), as observed in this case. The desertification of the PA-arid site represents a drastic and persistent environmental change, analogous to a freshwater exclusion experiment for mangroves of the tropical Brazilian coastline, in which this limitation probably caused the rapid evolution of recolonizing A. germinans individuals.…”
Section: Gradual Environmental Variation In Freshwater Availabilitymentioning
confidence: 71%
“…Although it is difficult to demonstrate rapid evolution in nature, there is growing empirical evidence that when environmental selection is very intense, evolutionary processes may occur on a very fast time scale (Amorim et al, 2017;Donihue et al, 2018;Schoener, 2011), as observed in this case. The desertification of the PA-arid site represents a drastic and persistent environmental change, analogous to a freshwater exclusion experiment for mangroves of the tropical Brazilian coastline, in which this limitation probably caused the rapid evolution of recolonizing A. germinans individuals.…”
Section: Gradual Environmental Variation In Freshwater Availabilitymentioning
confidence: 71%
“…The evolutionary dynamics highlighted in our model can also be useful for identifying potential threats of extinction in species of concern, and for designing more effective conservation actions. For example, two populations of the endemic Turks and Caicos anole, Anolis scriptus , were recently shown to have evolved larger toepads and shorter limb lengths (i.e., traits that increase these lizards' ability to cling to branches during strong winds) after two record‐breaking hurricanes (Donihue et al, ). These populations also exhibited a reduction in trait variance, suggesting that natural selection had favored individuals that were less likely to be blown away by hurricanes.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, they indicate that vulnerability to future changes in environmental cycles is likely to depend on the extent to which prior evolutionary history has promoted or not the evolution of phenotypes that can cope well with environmental extremes (Lawson, Vindenes, Bailey, & Pol, 2015;Olivieri, Tonnabel, Ronce, & Mignot, 2016). Although anthropogenic climate change is expected to result in longer, more severe, and/or more frequent extreme weather events (Hirabayashi et al, 2013;National Academy of Sciences, 2016;Stott, 2016;Trenberth, Fasullo, & Shepherd, 2015;Ummenhofer & Meehl, 2017), the extent to which populations may adapt to these changes is largely unknown (Donihue et al, 2018). To investigate this issue, we introduced a change in either flood height, flood scope, or probability of flooding at generation 2,000 and followed the resulting population dynamics and phenotypic evolution for an additional 200 generations.…”
Section: Prior Evolutionary History Determines Vulnerability To Chamentioning
confidence: 99%
“…A recent study further demonstrated that hurricanes can be selective agents driving the phenotype of anole populations that experience these extreme events. Specifically, Anolis lizards that survived hurricanes were shown to have large toepads, longer forelimbs but shorter hindlimbs than those that did not (Donihue et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Beyond toepads, clinging also appears to be related to limb length with longer limbed Anolis being better clingers as it allows them to wrap their arms across perches, thus providing a better grip (Kolbe, ). Although the exact mechanisms remain unclear, it has been suggested that larger toepads provide an advantage to arboreal Anolis lizards when clinging in high winds (Donihue et al ., ). If so, then survivors of extreme hurricanes are likely to show greater clinging strength and larger toepads than those that did not.…”
Section: Introductionmentioning
confidence: 97%